2017
DOI: 10.1515/mammalia-2016-0182
|View full text |Cite
|
Sign up to set email alerts
|

One or two species of the rare Malagasy carnivoran Eupleres (Eupleridae)? New insights from molecular data

Abstract: Members of the genus Eupleres are poorly known insectivorous carnivorans belonging to the family Eupleridae (order Carnivora), which are endemic to Madagascar. Recently, using morphological characters, the two previously recognized subspecies of Eupleres goudotii were raised to the species level, with E. goudotii occurring in the humid forests of the island, largely in the east, and Eupleres major in northwestern dry deciduous forests. Using some of the few museum specimens and fresh tissue samples available f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Second, unaccounted speciation of modern euplerids also may lead to underestimation of diversification rates. At least two euplerids— Eupleres goudotii and Salanoia concolor —are thought, though with uncertainty, to each consist of two species (i.e., E. goudotii and E. major and S. concolor and S. durrelli ) [40,41,81]; if valid, this would lead to increased diversification rates, albeit at more crownward tips of the tree. Lastly, euplerid diversification is perhaps better characterized as a continental radiation rather than as an insular radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Second, unaccounted speciation of modern euplerids also may lead to underestimation of diversification rates. At least two euplerids— Eupleres goudotii and Salanoia concolor —are thought, though with uncertainty, to each consist of two species (i.e., E. goudotii and E. major and S. concolor and S. durrelli ) [40,41,81]; if valid, this would lead to increased diversification rates, albeit at more crownward tips of the tree. Lastly, euplerid diversification is perhaps better characterized as a continental radiation rather than as an insular radiation.…”
Section: Discussionmentioning
confidence: 99%
“…These molecular techniques can be applied to museum specimens, so that it is possible to look at the genetics of specimens collected tens to hundreds of years ago to resolve taxonomic issues to benefit species today. For example, two species of Eupleres are often recognized – Eastern falanouc Eupleres goudotii and Western falanouc Eupleres major – but a recent genetic study based on museum specimens has questioned whether two species can be recognized (Veron & Goodman, 2018). These taxonomic revolutions are now fully accepted in current research (e.g.…”
Section: Taxonomymentioning
confidence: 99%
“…Taxonomic revision should be based on a diversity of data, such as morphology, mitochondrial and nuclear data, and distribution; unfortunately, for many species of small carnivores, these data are scarce (see e.g. Veron & Goodman, 2018). However, several recent phylogeographical studies have provided insights into the history of geographical lineages, and have also been helpful in the delineation of small carnivore species; for example, Small Indian mongoose Urva auropunctata and Javan mongoose Urva javanica (Veron et al ., 2007; Veron & Jennings, 2017), White‐nosed coati Nasua narica (Nigenda‐Morales et al ., 2019) and see below.…”
Section: New Species Of Small Carnivoresmentioning
confidence: 99%
“…This species included two subspecies – Eupleres goudotii goudotii , found in eastern Madagascar, and Eupleres goudotii major , localized in the north west of the island – that were raised to species level by Goodman & Helgen (2010) based on their morphology and distribution. Using genetic data, mainly from museum specimens, Veron & Goodman (2018) did not find any genetic structure within the genus, and thus suggested that this genus includes only one species – E. goudotii .…”
Section: New Species Of Small Carnivoresmentioning
confidence: 99%
See 1 more Smart Citation